Kaplan and Sadock's Study Guide and Self-Examination Review in Psychiatry - Sadock, B. J. Benjamin James (Wolters Kluwer, 2011)
Whether used in conjunctoin with Kaplan & Sadock's synopsis of psychiatry, 10th edition, or as a stand-alone review book, this revised and updated study guide in an excellent aid in preparing for boards and other psychiatry exans. Over 1,500 multiple-choice questions are designed to examine the etiology, diagnosis, and treatment of every known psychiatric disorder, with discussins of correct and incorrect answers.